Enzymatic synthesis and tailoring lignin properties: A systematic study on the effects of plasticizers. (12th August 2020) - Jimenez Bartolome, Miguel; Bischof, Sabrina; Pellis, Alessandro; Konnerth, Johannes; Wimmer, Rupert; Weber, Hedda; Schwaiger, Nikolaus; Guebitz, Georg M.; Nyanhongo, Gibson S.
Abstract: This work elucidates for the first time the effects of incorporating various concentrations of plasticizers having different chain length on the mechanical properties of fully enzymatically-synthesized lignosulfonate-based materials (LigMat). Laccase extensively polymerized lignosulphonates from an average 40 kDa up to >600 kDa resulting in water-insoluble polymers. Incorporation of plasticizers (malic acid, polyethylene glycol (PEG) having various molecular weights: PEG 200, PEG 400, PEG 600, PEG 1 K, PEG 20 K, sorbitol, glycerol and xylitol) into the synthesized lignosulphonates materials prevented its brittleness and generally improved the tensile and elongation properties of the polymers. The polymers supplemented with polyethylene glycol (PEG) having molecular weight ranging from 200 to 20 KDa consistently showed increasing tensile strength from an average of 20 MPa in polymers supplemented with 2.5%w/w to 74 MPa in polymers supplemented with 10%w/w plasticizer. Similarly, PEG also consistently led to increasing elongation at break from an average 16% in polymers supplemented with 2.5%w/w to 51% in polymer supplemented with 10%w/w plasticizer. However, although glycerol led to poor tensile strength properties, it had the longest elongation at break of 111%. This study indeed shows that plasticizers are efficient in modifying the strong intra- and inter hydrogen lignin molecule interactions thereby improved flexibility and the elasticity of the synthesized lignin materials. Graphical abstract: Image 1 Highlights: Laccase polymerizes lignin into high molecular weight insoluble polymers. Laccase polymerization of lignin increase viscosity of polymer. Laccase synthesis of 100% lignin based materials. Bio-based plasticizers enhances mechanical properties of lignin materials. Lignin materials have different properties depending on plasticizer used.